Strengthening Students' Character through Narrative Story Analysis: A Community Service Program at SMAN 8 Padang - Widya Juli Astria; Yessy Marzona; Feby Meuthia Yusuf; Lailatul Husna; Sherly Franchisca; Elda Martha Suri (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to improve students' understanding of moral values and to strengthen their character through story-based learning. The program was carried out at SMAN 8 Padang, targeting ninth-grade students through training in story analysis using a critical narrative analysis approach. A participatory action approach was applied in the form of interactive workshops and Focus Group Discussions (FGD), with the training materials focused on narrative texts, the identification of moral values, and the reinforcement of characters' traits. The results show that students were able to identify the moral values embedded in the stories, particularly honesty, responsibility, cooperation, and empathy, and to relate them to their everyday lives. The activity also encouraged students to think more critically in evaluating the moral consequences of the characters' actions. These findings indicate that story-based moral value analysis training is an effective learning strategy to support the Character Education Strengthening (Penguatan Pendidikan Karakter) program in secondary schools.